Readings in the strategy process - Mintzberg, Henry; Quinn, James Brian 1928-2012; Mintzberg, Henry (Prentice Hall, 1998)
This collection of readings, edited by Henry Mintzberg, presents an up-to-date look at how actual companies act strategically and the research driving them. While retaining many of the classic articles, this new edition includes the most exciting new organization and strategy concepts to emerge in the last few years: Core Competency Strategies; Strategic Outsourcing; Managing with the new digital technologies; and Managing Hypercompetition. An excellent resource for Business Managers and students of Business.